Integrated circuit design of readout interfacing circuit for MEMS resonator characterization: article / Maya Abu Bakar - Abu Bakar, Maya (2013)
This project presents the integrated circuit design for MEMS resonator with focused investigation on its application in on-chip MEMS resonator characterization. It is reported that MEMS resonator sensors vibrate at specific natural frequencies under different conditions. A readout interface circuit to capture this response that is designed for integrated circuits to reduce a lot of interference and for convenience of on-chip characterization.The analog circuit module will be designed using custom integrated circuit design approach from schematics to layout using Mentor Graphics tools and Silterra 0.13 µm technology files. The main sub circuit involved is operational amplifiers. The series RLC equivalent circuit is used to emulate the MEMS resonator to characterize the behavior of resonator. The drive frequency will be swept and match to the resonant frequency of MEMS resonator will cause the MEMS resonator produce the maximum current signal.